Navigating the Journey in Budgeting: Major Steps in Making a Complex Subject Manageable - Ursu, Christopher (Rowman & Littlefield Publishers, 2023)
As local education agencies, school districts are charged with educating students so that they are equipped with the knowledge and skills to be productive members of society as future adults. This goal is accomplished by providing an array of instructional and related services. To ensure that adequate resources are available for these services, a financial plan, or budget, must be in place. This book offers a roadmap for developing a school district budget, breaking an otherwise complex process down into a series of manageable steps. After going over general budgeting applications, concepts and techniques and providing a background in school district operations and finances, the book lays out a set of recommended procedures to take the budget from inception to completion. The book is intended for use by school business administrators, superintendents, school boards, and other school leaders as well as college students pursuing careers in public administration, business administration, or finance.